Lenguaje oral en niños de 5 años diestros y zurdos de la Red N° 8 - Callao - Carpio Cavero, Fryda Benedicta (2012)
This research was conducted in order to determine whether there were differences in the spoken language of right and left handed children. The research is a descriptive type and the design is descriptive-comparative. The intentional type sample consisted of 60 boys and girls of 5 years old from public schools, kindergarten level. First, the test of laterality of M. Auzziah was applied to corroborate the laterality of the child and then the test for the evaluation of oral language (ELO), adapted for Lima and Callao, which measures: auditory discrimination, phonological, syntactic and semantic aspects. Statistical tests used were the normality Kolmogorov-Smimov for verification of results and the U Mann Whitney to compare independent groups. The results showed that there are no significant differences of spoken language between left-handed and right-handed, concluding that both groups have the same level of skills in their oral language.